(untitled) (Pulse, 2024)
18F-fluorodeoxyglucose (18F-FDG) Positron Emission Tomography/- Computed Tomography (PET/CT) scan of oncological patients for the evaluation of disease status and treatment response has become a standard procedure of care. Abnormally increased 18F-FDG uptake represents abnormal findings. However, the area of increased uptake is not always associated with pathology. One such condition is the “hot clot artifact” or “pulmonary microembolism” in which there is intense focal FDG uptake in the lung without any corresponding CT-detectable structural lesion. Awareness of this condition is essential because it may cause misinterpretation as lung metastasis. Herein, we present a case showing focal FDG uptake in lung parenchyma without any structural lesion on CT scan, which subsequently resolved in follow-up imaging. Our case strengthens the importance of knowledge of this finding as misinterpretation of this can have a significant effect on patient management. Pulse Vol.15, 2023 P: 41-44